A study on a proposed new bus terminal in Green Town, Ipoh / Latif Mat Noor - Mat Noor, Latif (1990)
At present, there are 7 bus terminals in Ipoh. Jalan Silibin, Medan Kidd and Bangun Tajuddin Ali are the most important terminals. Jalan Silibin terminal i.e. the main terminal is mainly for local service and outstation service, also two express service – Telok Anson and Taiping. Medan Kidd is for southbound, northbound buses and eastbound express buses and Bangunan Tajuddin Ali is exclusively for the west bound, Jalan Bendahara, Jalan Leong Sin Nam dan Jalan Yang Kalsom are exclusively for southbound and Jalan Clare is exclusively for local bus service. Jalan Silibin is a public bus terminal located in the outskirt of CBD of Ipoh near the roundabout connecting Jalan Silibin, Jalan Panglima Bukit Gantang Wahab and Jalan Kidd.